The Influence of Original Local Government Revenue, Specific Allocation Fund on Government Capital Expenditures in Southeast Sulawesi Disrict/ City - Erwin Hadisantoso; Arifuddin Arifuddin; Andi Basru Wawo; Muh. Ridwan (Politeknik Ganesha Medan, 2023)
This study aims to examine how the influence of Local Own Revenue and Special Allocation Funds on District/City Government Capital Expenditures in Southeast Sulawesi Province. The type of data used in this study is secondary data. The source of the data used in this study comes from Realization Reports on the Capital Expenditure Budget, Local Own Revenue and Special Allocation Funds from 2015-2021 in 17 Regencies/Cities in Southeast Sulawesi Province. Analysis of testing the data in this study is panel data regression analysis using Eviews 10 software. The results of this study found that the Regional Original Income variable has a significant effect on the Capital Expenditure variable with a significant level of 0.0000, the Special Allocation Fund variable has a significant effect on the Capital Expenditure variable with a significant level of 0.0000. As well as the variable Regional Original Income and Special Allocation Funds Simultaneously or jointly have a significant effect on the Capital Expenditure variable with a significant level of 0.00000. The limitations of this study are that there are still many factors that influence Capital Expenditures, therefore it is hoped that further researchers can add other variables to make them more varied.